Ferromagnetic ordering in diluted magnetic semiconductors - Slobodskyy, A.H.; Dugaev, V.K.; Vieira, M. (Condensed Matter Physics, 2002)
We present a general approach to the problem of a ferromagnetic phase
transition in diluted magnetic semiconductors. The Curie temperature of
ferromagnetic transition is calculated in the mean field approximation. It is
shown that the Curie temperature is determined by an integrated coupling
between magnetic impurities. Запропоновано загальний підхід до проблеми феромагнітного фазового переходу в легованих магнітних напівпровідниках. Температуру Кюрі феромагнітного переходу обчислено в наближенні середнього поля. Показано, що температура Кюрі визначається через інтеграл від парної взаємодії між магнітними домішками.